Effect of organic sources of nutrients on performance of soybean (Glycine max) - AHER, S B; LAKARIA, BRIJ LAL; SINGH, A B; KALESHANANDA, SWAMI; RAMANA, S; RAMESH, K; THAKUR, J K; RAJPUT, P S; YASHONA, D S (The Indian Journal of Agricultural Sciences, 2019)
A field experiment was conducted at the Research Farm of ICAR-Indian Institute of Soil Science, Bhopal, India to study the effect of different combinations of organic inputs on performance of soybean [Glycine max (L.) Merr.]. Soybean (cv. JS 335) was grown in a randomized block design with seven treatments and four replications. The treatments studied were organic manure (OM) (T1); biodynamic preparation (BD) (T2); OM+panchagavya (OM+PG) (T3); OM+BD (T4); OM+PG+BD (T5); control (T6); and recommended dose of fertilizers (RDF) (T7). The results of the study revealed that, the treatments with organic manures either alone or in combination with panchagavya and/or biodynamic application improved the performance of soybean crop. The yield of soybean was found comparable and even better (higher 5–13%) with those obtained under RDF, which enhanced nutrient removal by soybean crop by 5–13% with organic combinations. Similarly, the application of organic manures significantly improved the available nutrient status of soil and showed 19–22% and 28–33% higher available N and P, respectively than RDF. Soil enzyme activities, viz. dehydrogenase and alkaline phosphatase increased by 62–72% and 27–35%, respectively under the treatments receiving organic source of nutrients over RDF.